2019
DOI: 10.1016/j.ajpath.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Follicular Bile Acids in the Human Ovary

Abstract: Number of figures: 6 Number of tables: 1 Short running head: Origin of ovarian follicular bile acids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In addition, the activation of FXR induces apoptosis of germ cells by decreasing testosterone synthesis [ 16 ] or suppresses sperm production by maintaining an undifferentiated germ cell pool in an androgen-independent manner [ 17 ]. In females, the roles of BAs on oocyte maturation are still unknown, however effects are suspected [ 18 ]. Though, the deactivation of TGR5 and FXR by UDCA treatment did not improve the low pregnancy rate of the DKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activation of FXR induces apoptosis of germ cells by decreasing testosterone synthesis [ 16 ] or suppresses sperm production by maintaining an undifferentiated germ cell pool in an androgen-independent manner [ 17 ]. In females, the roles of BAs on oocyte maturation are still unknown, however effects are suspected [ 18 ]. Though, the deactivation of TGR5 and FXR by UDCA treatment did not improve the low pregnancy rate of the DKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that FXR is also expressed in mouse ovarian granulosa cells and that FXR can regulate the function of granulosa cells by acting on target genes such as SHP and FABP6 ( 23 ). Another study discovered that the bile acids can be transported from the blood to the follicular fluid and have an impact on the reproductive system ( 24 ). Schuermann et al ( 25 ) used metabolomics to show that metabolites like bile acids are present in the follicular fluid of cows and suggested that these metabolites may be involved in regulating reproductive performance at different physiological stages in cows.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DNA methylation mediates cell responses to physiological endocrine signals, so epigenetic changes produced during development might affect persistently endocrine function (García-Carpizo et al, 2011 ). In addition, BAs also have hormonal actions throughout the body, particularly through the farnesoid X receptor and GPBAR1 (also known as TGR5), playing an important role in the regulation of intrafollicular steroid production (Nagy et al, 2019 ), so the different composition of BAs observed in F1-RES might be partially responsible for the low-progesterone concentration. In any case, two functional categories of genes related to reproduction (e.g., mating and response to estrogens) were significantly enriched in F1-RES lambs.…”
Section: Discussionmentioning
confidence: 99%